Pemidanaan Tindak Pidana Perikanan Berbasis Kerugian Ekonomi - Nurul Hudi (Faculty of Law Hang Tuah University, 2021)
Fisheries criminal law enforcement is part of criminal policy or criminal policyIn Law Number 31 of 2004 in conjunction with Law Number 45 of 2009 concerning Fisheries. The type of punishment known is only the principal punishment, namely imprisonment and fines. This law does not use additional penalties.In punishing the perpetrators of fisheries crimes, it must be understood more deeply and the basis of the punishment must be known.One of the efforts to overcome crime is to use criminal law with criminal sanctions. However, this effort is still often questioned. Punishment is more oriented to the perpetrator while the losses from criminal acts are sometimes neglected. Criminal law policies in the field of fisheries, especially those related to punishment or criminal penalties, must also consider losses from the economic, social and sustainability aspects of fisheries.